Strategi Guru Pendidikan Agama Islam Dalam Menumbuhkan Nilai–Nilai Profil Pelajar Pancasila di SMPN 29 Rejang Lebong - Mahardika, Mutiara; Meiyanda, Rana; Ashabul Jannah, Wahyu; Rahmi Nasution, Aida; Daheri, Mirzon (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study analyzes the strategies used by Islamic Education (PAI) teachers in fostering the values of the Pancasila Student Profile at SMPN 29 Rejang Lebong. The research aims to identify effective strategies, their implementation, and the challenges encountered. Using a qualitative case-study design, data were collected through interviews, observations, and documentation with purposively selected participants. The analysis employed interactive techniques consisting of data reduction, data display, and conclusion drawing. The findings show that modeling, habituation, and value integration into learning are the dominant strategies that strengthen students’ religious, social, and collaborative attitudes. Daily prayer routines, tadarus, multicultural discussions, and social activities contribute to increased discipline, tolerance, and cooperation among students. These results align with theories of social learning, multicultural education, and character development, as well as prior studies emphasizing the role of modeling and experiential learning in character formation. The study suggests that character education can be effectively implemented even with limited facilities, provided teachers apply consistent, contextual, and participatory approaches. Supplementary materials include interview excerpts and observation notes.